Molecular basis for the tissue-specificity of β-catenin oncogenesis - Sharma, Archna (2012)
Wnt-β-catenin-T Cell Factor signaling is causally linked to c-myc dependent tumorigenesis in mouse and human colon epithelial cells. By contrast, β-catenin is not similarly associated with oncogenic transformation of other tissues, including T cells. The molecular basis for tissue specificity of β-catenin dependent oncogenesis is unknown. Here we demonstrate that Adenomatous Polyposis Coli mutant APC(Min/+) mice, which have increased expression of β-catenin in all tissues, develop severe intestinal neoplasia, but fail to develop thymic lymphoma. Whereas β-catenin elicits a proliferative response from intestinal cells, thymocytes experience oncogene-induced-senescence (OIS), growth arrest and apoptosis. We demonstrate that the differential cellular response of thymocytes and intestinal epithelial cells is a direct consequence of the gene expression elicited by β-catenin expression in each tissue. We find that whereas intestinal cells induce genes that promote proliferation thymocytes induce expression of genes associated with OIS, growth arrest and p53-dependent apoptosis. We correlate gene expression pattern with the role β-catenin plays in the development of each tissue and suggest that susceptibility of transformation by β-catenin is intimately related to its function during development. We propose that when oncogenes are used as signaling molecules, safety nets in the form of OIS, growth arrest and apoptosis are in place to prevent accidental transformation.